An experimental and computational comparison of the dynamic response variability in a turbine blade with under-platform dampers. (1st June 2022) - Ferhatoglu, Erhan; Gastaldi, Chiara; Botto, Daniele; Zucca, Stefano
Abstract: In this paper, the nonlinear response variability in turbine bladed disks coupled with under-platform dampers (UPDs) is both numerically and experimentally investigated in detail. Non-uniqueness uncertainty of contact forces, which leads to different static force equilibria under the same nominal conditions, is shown as the main source of multiple responses. In the experiments, a previously designed test rig consisting of one blade and two UPDs is used to reveal the inherent kinematics of the friction force uncertainty. A large variability range is achieved in different tests while keeping all user-controlled inputs identical. On the computational side, the boundaries of the variability range are predicted by utilizing a recently developed numerical method. The loss factor of the system is exploited as an objective function to be minimized through an optimization algorithm. To compare the results, several cases with different excitation levels and pre-loads are studied. It is shown in most of the cases that the method is well-suited for the computation of nonlinear response boundaries. Experimentally measured variability range of the dynamic responses and contact forces is computationally obtained with a satisfactory level of accuracy. A slight deviation is also reported in few cases, particularly for highly nonlinear ones where the numerical model is not fully capable of replicating the non-ideal conditions achieved during the tests.